The Processing and Application of Calcium phosphate-based Bioceramics: A Review - Ibrahim Etbeni,; Abdulmoneim Kazuz,; Mohamed Elalem,; Fathi Elhadi, (AlQalam Journal of Medical and Applied Sciences, 2025)
This review provides a comprehensive overview of the processing, properties, and applications of calcium phosphate (CaP)-based bioceramics in dentistry. It focuses on key materials such as hydroxyapatite (HA), fluorapatite (FAp), and tricalcium phosphates (α-TCP and β-TCP), which are central to modern restorative and regenerative strategies due to their compositional and structural similarity to natural bone and enamel. The paper examines the fundamental properties of bioceramics, including their biocompatibility, osteoconductivity, and bioactivity. Concurrently, it addresses their inherent mechanical limitations, primarily brittleness, which restricts their use in high-stress, load-bearing applications. Strategies to overcome these challenges are detailed, including the development of composites with polymers and other ceramics, as well as chemical modifications like ion doping (e.g., Ag+, Sr2+) to impart antimicrobial properties and fluorine substitution to form more acid-resistant fluorapatite. A wide range of dental applications is discussed, from their use in remineralizing toothpastes and serving as bioactive coatings on titanium implants to enhance osseointegration, to their fabrication into porous scaffolds for bone tissue engineering and drug delivery. The outlook suggests the development of multifunctional, customized materials through advanced fabrication techniques, such as 3D printing and nanotechnology, to create active therapeutic systems that can heal, prevent disease, and withstand the demanding oral environment.